Effects of graphene oxide plus external bacterial agents on accelerating poplar leaf-litter decomposition in saline–alkali soil - Qiao, Jun; Liu, Jiahao; Chen, Xiaokang; He, Xianbo; Zhao, Jianguo; Ma, Guibin (Frontiers in Soil Science, 2025)
Poplar trees and saline–alkali soil commonly occur in northern China, especially around the Datong district in northern Shanxi. To better utilize this type of soil, it is important to know how to neutralize saline–alkali conditions and how poplar leaves decompose in this soil media. Graphene oxide (GO) is widely known for improving soil nutrient content in agricultural and forestry soils. Here, we examined the effect of a graphene oxide composite combined with the addition of external bacterial agents on the decomposition of poplar leaves in saline–alkali soil. A litterbag method was used, and content analyses were conducted on both the litter residue and the decomposed soil at different sampling times. Overall, the humus content of the leaf-litter–decomposed soil gradually increased over time. Meanwhile, the total nitrogen, phosphorus, ammonium nitrogen, available potassium, and most phosphorus contents showed a trend of initially decreasing slightly and then gradually increasing. Nutrient concentrations, as well as humus content in the soil, reached their maximum after 120 days with the addition of both 25.0 mg/L GO and microbial agents. We conclude that the combination of GO and microbial agents promotes soil enzyme activity and accelerates litter decomposition, with the highest enzyme activity observed when both 25.0 mg/L GO and bacterial agents were present in the saline–alkali soil.